MIMO Antenna for Wireless Applications - Sravani, Sirigiri; Supriya, M. G.; Gudi, Srinidhi; Gupta, Sushant; Anitha, V. R. (International Journal of Recent Advances in Multidisciplinary Topics, 2023)
MIMO antenna is currently the focus of a lot of research because of its potential to increase the capacity and dependability of the wireless communication system. Despite the advantages, mutual coupling still presents a significant obstacle. Mutual coupling is normally undesired because it has an impact on the MIMO antenna and antenna array system’s performance. By increasing mutual coupling, envelop correlation coefficient, channel capacity loss, diversity gain, and radiation pattern distortion, the interaction of the array elements and MIMO elements reduces system performance. When antennas are put close together, this issue could occur. A MIMO antenna has at least two radiating elements that are evenly spaced apart in order to achieve good isolation between them. But practical portable gadgets cannot fit in the space that is provided. Numerous methods have been used to reduce the mutual coupling between MIMO elements in this regard. The isolation in the suggested design is accomplished by sandwiching a number of metamaterial unit cells between the two antennas. Very little mutual coupling (|S21/S12| 20 dB) characterizes the proposed antenna. Considering that it has a low ECC, high diversity gain, high peak gain, low channel capacity loss, and the majority of importantly, its extremely high isolation, the proposed MIMO antenna is well-suited for the diverse wireless application possibilities.